WOMEN AND HEALTH: TRAUMA AND CHRONIFICATION IN MOTHERS OF DISABLED CHILDREN - Limiñana Gras, Rosa María; Patró Hernández, Rosa (Anales de Psicología / Annals of Psychology, 2004)
In our social context women have to face many difficulties which have a temporary and a permanent effect on their daily lives. In our research we have studied a very specific sample of people who suffer from a serious psychological trauma. They are mothers of children who suffer from a congenital disability, which is the Spina Bifida in its most serious state, the mielomeningocele. On the whole, results show the existence of preferential psychological styles which are directly related to the disability and which enable us to analyse differences regarding gender. These differences suggest that a child’s disability has a differentimpact on men and women. Impact on women can also be assesed.